كيفية حساب الاجر والراتب لدى مديرية التربية - عفاف, عشاب; طارق, بن عبيد; فريدة, عيساوي; ريحانة, العايز (جامعة الوادي - University of Eloued, 2023)
في هذا الفصل قمنا بتعريف المؤسسة محل دراسة وتطرقنا إلى نشأتها ومهاهما وانجازاتها المحققة وهيكل التنظيمي ثم خصصنا دراسة بمصلحة نفقات المستخدمين وبعد الاطلاع على نظم سير عملية حساب الاجور والرواتب بناءا على النصوص التي تحكم قطاع التربية والاضافات وتغيرات الحديثة على جدول الضريبة على الدخل وأيضا كيفية حساب الاجور والرواتب وكيف تسدد المؤسسة هذه الأعباء على عاتق المؤسسة. In this chapter, we defined the institution under study and touched on its inception, missions, achievements and organizational structure, then we devoted a study to the interest of employees’ expenses and after examining the systems for the process of calculating wages and salaries based on the texts that govern the education sector, additions and recent changes to the income tax schedule, as well as how wages are calculated Salaries and how the institution pays these burdens is the responsibility of the institution.
Keywords: الاجور والرواتب, الاقتطاعات , التعويضات , المنح والعلاوات.; Wages and salaries, deductions, compensation, grants and bonuses.